Short‐stay hospital admission after free tissue transfer for head and neck reconstruction. (26th July 2016) - Devine, Conor M.; Haffey, Timothy M.; Trosman, Samuel; Fritz, Michael A.
Abstract : Objectives/Hypothesis: To show that, for patients with few medical comorbidities and at low risk for airway compromise or fistula formation, early discharge after free tissue transfer for head and neck reconstruction is a safe and viable option. Study Design: Retrospective chart review. Methods: A cohort of patients who underwent free tissue transfer for head and neck reconstruction between February 2010 and December 2014 and who were discharged from the hospital by postoperative day 3 were reviewed. Results: Fifty patients undergoing 51 free‐tissue transfer surgeries were discharged by postoperative day 3. The surgeries performed included anterolateral thigh free flaps (ALT) (n = 46), radial forearm free flaps (n = 2), latissimus myogenous and myocutaneous free flaps (n = 1), supraclavicular free flap (n = 1), and serratus free flap (n = 1). All ALT flaps were harvested exclusively as perforator free flaps; and the vast majority used superficial temporal, angular, or facial vessels. All free flaps were viable without evidence of vascular compromise at discharge and the initial follow‐up appointment. One patient required take‐back for successful flap salvage. One patient experienced late flap failure (between 2–3 weeks postoperatively), requiring another surgery. This resulted in an overall success rate of 98% in this cohort. No other postoperative complications related to early discharge were identified. Conclusion: In a carefully selected subset of patients undergoing free tissue transfer, early discharge has been shown to be possible without compromising patient safety or surgery success rates. Level of Evidence: 4. Laryngoscope, 126:2679–2683, 2016